2019
DOI: 10.1111/jvim.15679
|View full text |Cite
|
Sign up to set email alerts
|

Clinical features and outcome in 25 dogs with respiratory‐associated pulmonary hypertension treated with sildenafil

Abstract: Background: Pulmonary hypertension (PH) can develop secondary to many common cardiopulmonary diseases, and the use of sildenafil has improved care of affected dogs.Objective: To evaluate response to sildenafil in dogs with respiratory-associated PH.Animals: Twenty-five dogs with PH.Methods: Prospective clinical trial. Doppler echocardiography identified dogs with moderate to severe PH, and additional tests were performed to detect underlying diseases. A 17-point quality of life (QOL) questionnaire was complete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The most likely explanation for the lack of association between survival and PH in our cohort of WHWTs affected with CIPF is that all WHWTs affected with CIPF suffering from PH at diagnosis were subsequently treated with sildenafil and then regularly followed as part of the CIPF-project to adjust treatment recommendations. Sildenafil treatment in pre-capillary PH has been shown to lower PAP from baseline, improve quality of life, and expand likelihood of survival in dogs [ 21 23 ]. Accordingly, sildenafil administration in our cohort of CIPF WHWTs affected with pre-capillary PH could have contributed to improved survival and prevented identification of an association between the presence of PH at diagnosis and outcome.…”
Section: Discussionmentioning
confidence: 99%
“…The most likely explanation for the lack of association between survival and PH in our cohort of WHWTs affected with CIPF is that all WHWTs affected with CIPF suffering from PH at diagnosis were subsequently treated with sildenafil and then regularly followed as part of the CIPF-project to adjust treatment recommendations. Sildenafil treatment in pre-capillary PH has been shown to lower PAP from baseline, improve quality of life, and expand likelihood of survival in dogs [ 21 23 ]. Accordingly, sildenafil administration in our cohort of CIPF WHWTs affected with pre-capillary PH could have contributed to improved survival and prevented identification of an association between the presence of PH at diagnosis and outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Pulmonary hypertension (PH) is a secondary complication of many commonly encountered cardiopulmonary disorders and is an increasingly recognized clinically important finding in dogs. [1][2][3][4][5] It is commonly associated with and can lead to clinical signs such as exercise intolerance, breathing difficulty, and exertional syncope and can cause right heart failure. [4][5][6][7][8][9][10] Reports have suggested that a tricuspid regurgitation pressure gradient (PG) > 55 mm Hg and ≥47 mm Hg is associated with an increased risk of death in dogs with myxomatous mitral valve disease (MMVD) 5 and respiratory disease/hypoxia, 4 is the primary metric used to estimate pulmonary arterial pressure and helps to assess the echocardiographic probability a dog has PH.…”
Section: Introductionmentioning
confidence: 99%
“… 26 This survey was successfully applied to dogs with respiratory disease in a study of pulmonary hypertension. 27 The FETCH survey provides assessment of QOL with significant overlap in clinical signs observed in both cardiac and respiratory disease but does not evaluate cough in depth. Therefore, at the time of enrollment, 2, 4, and 6 weeks, owners also completed a cough survey, which assessed cough characteristics (frequency, duration, severity), ease of administration of inhaled medications, and corticosteroid‐related adverse effects using a visual analog scale (VAS; Figures S1 and S2 ).…”
Section: Methodsmentioning
confidence: 99%